Milieu Therapy as an Effort to Prevent Burnout Events in Nurses - Shindi Hapsari; Tri Ismu Pujiyanto; Eko Ristiarso; Aprin Rusmawati (Journal Of Nursing Practice, 2025)
Background: Nurses have a high workload, so they are at risk of burnout. One of the non-pharmacological therapies that can overcome burnout is Milieu therapy.  Purpose: This study aims to determine the effect of Milieu therapy on reducing the incidence of burnout in nurses in the inpatient room of Melati RSUD Batang. Methods: This study is pre-experiment research with One-Group Pretest-Posttest design using the Maslach Burnout Inventory questionnaire. The intervention was carried out 1 time per shift with a duration of 20 minutes for 7 days. The study used a total sampling of 18 implementing nurses in the Melati room of RSUD Batang. Data analysis using the Wilcoxon test. Results: The average burnout rate before Milieu therapy was 45.22 and after 42.28. The results of the Wilcoxon test obtained p value = 0.001, it can be concluded that there is an effect of Milieu therapy on reducing the incidence of burnout in nurses in the Melati inpatient room of RSUD Batang. Conclusion: Milieu therapy can be applied as an effective nonpharmacological therapy in treating burnout in nurses.